2006
DOI: 10.1124/jpet.106.102004
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Protein Kinase c-Src Reduces the Incidence of Breast Cancer Metastases and Increases Survival in Mice: Implications for Therapy

Abstract: c-Src is a proto-oncogene, belonging to the nonreceptor protein kinases family, which plays a prominent role in carcinogenesis. In this study, we tested the hypothesis that c-Src could promote breast cancer metastasis acting on several cell types and that pharmacological disruption of its kinase activity could be beneficial for the treatment of metastases. Female BALB/cnu/nu mice were subjected to intracardiac injection of the human breast cancer cells MDA-MB-231 (MDA-231), which induced prominent bone and vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
102
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(108 citation statements)
references
References 29 publications
6
102
0
Order By: Relevance
“…4b). BALB/c-nu/nu mice were subjected to intracardiac injection of MDA-MB-231 cells and treated with CGP76030, which, as expected, significantly reduced the incidence of bone metastases compared with untreated mice 17 ( Fig. 4c).…”
Section: Role Of the Interplay Between C-src And Il-6 In Bone Metastasupporting
confidence: 69%
See 3 more Smart Citations
“…4b). BALB/c-nu/nu mice were subjected to intracardiac injection of MDA-MB-231 cells and treated with CGP76030, which, as expected, significantly reduced the incidence of bone metastases compared with untreated mice 17 ( Fig. 4c).…”
Section: Role Of the Interplay Between C-src And Il-6 In Bone Metastasupporting
confidence: 69%
“…A potential therapeutic impact could be predicted from these results, hypothesizing that a c-Src inhibitor could be used in cancer-induced bone diseases not only to impair osteoclast bone resorption and tumour cell proliferation 17,26,27 , but also to reduce IL-6 production and, therefore, its deleterious systemic effects on the body. Indeed, clinical trials are in progress for cancer using the c-Src inhibitor Saracatinib, which, in our opinion, associated with the IL-6 receptor-neutralizing antibody Tucilizumab, may open new avenues for combination treatment of patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overexpression of the non-receptor tyrosine kinase, Src, and/or an increase in its kinase activity has been associated with the development and progression of a number of human malignancies including breast cancer [12,13] where it has been implicated in metastatic progression [14]. Interestingly, it has recently been reported that expression of activated Src is associated with a reduced recurrencefree survival in ductal carcinoma in situ [15].…”
Section: Introductionmentioning
confidence: 99%